Ecological ICMS: analysis of alternatives for its implementation in the state of Bahia - Brazil - Novaes, Daniel Souto; Pires, Monica Moura (Sociedade & Natureza, 2020)
This paper analyzes alternatives for the implementation of ecological ICMS in the state of Bahia. With this purpose were estimated the values transferred to the municipalities of Bahia, as ICMS, according to the current rules (LCE 13/1997), comparing the situation observed with the implementation scenarios of bills n. 76/2006 and 15.502/2006 and through the use of a sustainability indicator proposed in this work. The calculations were made considering the years 2006 and 2016. In order to analyze the proposal for the sustainability indicator, an index was prepared for each municipality in Bahia, which, once used in the calculation of the ICMS transfer, was able to compensate financially the municipalities that adopt public policies to promote sustainability. For that, the Sustainable Development Indicator (IDS) was used. The results show that the implementation of the bills would bring disadvantages for the small number of criteria adopted, while the use of the IDS would facilitate the treatment of the municipal reality in a more holistic way. In any case, in all the analyzed situations the values destined to the ecological criteria are inexpressive in comparison to the criterion related exclusively to the municipal economic production.